CONFLICTS THE HARMONY OF MULTIETHNIC VILLAGE IN OVERCOMING - Yuyun Yunita; M Nasor; MA. Achlami Hs; Fitri Yanti (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
In everyday life, the basic identity of an ethnic group is often manipulated. Basic identity can possibly be deactivated, activated and also narrowed down because the basic identity is not something that is rigid like a stone but more like liquid, so it can flow and develop in order to make adjustment in life. But sometimes, the flow of basic identity can possibly crash strongly like a flood breaking the dams, and destroy everything that goes through. In certain circumstances, the basic identity which manifests its existence in the form of primodial bonds gives space to powerful emotional cohesion or excessive ethnocentrism, thus becoming a source of calamity.Based on the problems as above, multi-cultural government needs to offer an alternative based on diversity utilization in society. The importance of conducting this research is based on the objective conditions of preliminary research data, when this problem is ignored in this time, it can become a problem in the future, and conflicts can be avoided due to the application of multiethnic based areas.